Cross‐sectional analysis reveals autoantibody signatures associated with COVID‐19 severity. Issue 2 (15th February 2023) - Baiocchi, Gabriela C.; Vojdani, Aristo; Rosenberg, Avi Z.; Vojdani, Elroy; Halpert, Gilad; Ostrinski, Yuri; Zyskind, Israel; Filgueiras, Igor S.; Schimke, Lena F.; Marques, Alexandre H. C.; Giil, Lasse M.; Lavi, Yael B.; et al.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection is associated with increased levels of autoantibodies targeting immunological proteins such as cytokines and chemokines. Reports further indicate that COVID‐19 patients may develop a broad spectrum of autoimmune diseases due to reasons not fully understood. Even so, the landscape of autoantibodies induced by SARS‐CoV‐2 infection remains uncharted territory. To gain more insight, we carried out a comprehensive assessment of autoantibodies known to be linked to diverse autoimmune diseases observed in COVID‐19 patients in a cohort of 231 individuals, of which 161 were COVID‐19 patients (72 with mild, 61 moderate, and 28 with severe disease) and 70 were healthy controls. Dysregulated IgG and IgA autoantibody signatures, characterized mainly by elevated concentrations, occurred predominantly in patients with moderate or severe COVID‐19 infection. Autoantibody levels often accompanied anti‐SARS‐CoV‐2 antibody concentrations while stratifying COVID‐19 severity as indicated by random forest and principal component analyses. Furthermore, while young versus elderly COVID‐19 patients showed only slight differences in autoantibody levels, elderly patients with severe disease presented higher IgG autoantibody concentrations than young individuals with severe COVID‐19. This work maps the intersection of COVID‐19 and autoimmunity by demonstrating the dysregulation of multiple autoantibodies triggered during SARS‐CoV‐2 infection. Thus, this cross‐sectional study suggests that SARS‐CoV‐2 infection induces autoantibody signatures associated with COVID‐19 severity and several autoantibodies that can be used as biomarkers of COVID‐19 severity, indicating autoantibodies as potential therapeutical targets for these patients.